CO-MORBIDITY OF CARDIOVASCULAR DISEASES AND RHEUMATOID ARTHRITIS - PANDYA DT; Gc, Patel; Pp, Ambegaokar; Nd, Vyas (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Rheumatoid Arthritis (RA) is a chronic disease related to swelling of joints which leads to restriction in movement due to pain and deformity in mainly in feet, ankle, wrist and fingers. It is an autoimmune disease and the manifestations caused due to its occurrence are not clearly understood. In today's time, it has been observed that comorbid conditions account for most of the deaths as they influence the outcome of RA and limit therapeutic options. The most common comorbid conditions which are diagnosed in RA patients are generally cardiovascular abnormalities, several infections, certain mental disorders and malignancies. Among which cardiovascular comorbid diseases are the most common kind relating to disorders of heart and blood vessel that eventually leads to severe conditions like angina, myocardial infarction (MI), stroke, rheumatic heart disease and many more. RA affects the quality of life of patients directly or indirectly but it mainly shows a significant increase in the prevalence of cardiovascular diseases. Hence, it is essential to diagnose and understand about the related manifestations when one is suffering from Rheumatoid Arthritis. These studies will aid to make better treatment and management strategies. Hence, an attempt has been made in this review article regarding the epidemiology, impact of both the diseases and related risk factors. It also gives information in brief about the pathological causes of the comorbidity and summarizes measures that may be used in the prevention and treatment of these conditions.